2022
DOI: 10.4028/p-51to4o
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene on Mechanical and Morphological Properties of Coconut Shell Reinforced Unsaturated Polyester Composite

Abstract: Coconut shell (CS) reinforced unsaturated polyester (UPE) composites have been prepared by using hand lay-up and compression molding techniques. To improve fiber matrix adhesion, the CS (30 wt%) was chemically treated by two chemical treatments which are alkaline (NaOH) and alkaline-silane with concentration NaOH (6%) and silane (2%). To enhance the performance of CS-UPE composites, graphene nanoplatelets (GNP) was also added as a nano filler. Scanning electron microscopy (SEM) was used to investigate the morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Attiya et al [ 99 ] produced graphene composites with unsaturated polyester and reported an improvement in mechanical and thermal properties with graphene 1.5 wt.%, flexural strength increased from 45 to 65 MPa, and thermal conductivity increased from 0.2 to 0.5 WmK −1 . Abdullah et al [ 100 ] studied the mechanical properties of GNP/unsaturated polyester composites, and at 1 wt.% of GNP loading, they found that flexural strength decreased from 72 MPa (at 0.5 wt.%) to 60 MPa (1 wt.%), and they attributed this to the agglomeration of GNP, which might act as steric barriers.…”
Section: Processing Methodsmentioning
confidence: 99%
“…Attiya et al [ 99 ] produced graphene composites with unsaturated polyester and reported an improvement in mechanical and thermal properties with graphene 1.5 wt.%, flexural strength increased from 45 to 65 MPa, and thermal conductivity increased from 0.2 to 0.5 WmK −1 . Abdullah et al [ 100 ] studied the mechanical properties of GNP/unsaturated polyester composites, and at 1 wt.% of GNP loading, they found that flexural strength decreased from 72 MPa (at 0.5 wt.%) to 60 MPa (1 wt.%), and they attributed this to the agglomeration of GNP, which might act as steric barriers.…”
Section: Processing Methodsmentioning
confidence: 99%